Rapid magnetofluidic mixing in a uniform magnetic field - Zhu, Gui-Ping (2013)
This paper reports the investigation of mixing phenomena caused by the interaction between a uniform magnetic field and a magnetic fluid in a microfluidic chamber. The flow system consists of a water-based ferrofluid and a mixture of DI water and glycerol. Under a uniform magnetic field, the mismatch in magnetization of the fluids leads to instability at the interface and subsequent rapid mixing. The mismatch of magnetization is determined by concentration of magnetic nanoparticles. Full mixing at a relatively low magnetic flux density up to 10 mT can be achieved. The paper discusses the impact of key parameters such as magnetic flux density, flow rate ratio and viscosity ratio on the mixing efficiency. Two main mixing regimes are observed. In the improved diffusive mixing regime under low field strength, magnetic particles of the ferrofluid migrate into the diamagnetic fluid. In the bulk transport regime under high field strength, the fluid system is mixed rapidly by magnetically induced secondary flow in the chamber. The mixing concept potentially provides a wireless solution for a lab-on-a-chip system that is low-cost, robust, free of induced heat and independent of pH level or ion concentration.